Exploring interpersonal dynamics - Perrewe, Pamela L.; Ganster, Daniel C. (Emerald, 2004)
This is an annual research series devoted to the examination of occupational stress, health and well being, with particular emphasis on the multi-disciplinary nature of occupational stress. The intent is to pull together the various streams of research from a variety of disciplines to better capture the significant bodies of work in occupational stress and well being. We provide a multidisciplinary and international perspective that gives a thorough and critical assessment of issues in occupational stress and well being. The theme for this volume is: Exploring Interpersonal Dynamics. It covers - Workplace Aggression and Violence against Individuals and Organizations: Causes, Consequences, and Interventions; The Radiating Effects of Intimate Partner Violence on Occupational Stress and Well Being; The Changing Nature of Job Stress: Risk and Resources; Job Characteristics and Learning Behavior: Review and Psychological Mechanisms; Organizational Stress Through the Lens of Conservation of Resources (COR) Theory; The Role of 'Happiness' in Organizational Research: Past, Present and Future Directions; Display Rules and Strain in Service Jobs: What's Fairness Got to do With It? Stress and Well Being in the Context of Mentoring Processes: New Perspectives and Directions for Future Research.
Keywords: Business & Economics -- Management.; Psychology -- Applied Psychology.; Organizational theory & behaviour.; Social, group or collective psychology.; Interpersonal relations.; elektronické knihy; electronic books